Fasilitasi bantuan usaha ekonomi kreatif kelompok masyarakat binaan Balai Taman Nasional Bunaken di Pulau Nain - Lukman, Ermas Isnaeni (Dharma: Jurnal Pengabdian Masyarakat, 2022)
Community empowerment in buffer zone villages is one of the conservation-based development efforts. Community empowerment through the development of the creative economy is an alternative for the community in developing their local potential. Nain Island is the farthest island in the Bunaken National Park area which can only be accessed by sea from the mainland of North Sulawesi. This limited access needs to be supported by the development of infrastructure in terms of transportation, electricity, water, social, economic, education, health and environmental development. Economic crisis have a serious impact on the future of the existence of the national park, namely the level of education of the people in and around the conservation area. Recognizing the above, Bunaken National Park Center distributes various kinds of assistance for empowering community economic enterprises through fostered groups in all areas of management at the site level (resort). Groups that have been assisted previously for a sufficient period of time will then be tested for feasibility and readiness in terms of receiving assistance. The implementation of facilitation activities and the provision of creative economic business assistance to the assisted village community groups on Nain Island is carried out on an ongoing basis. The method of implementing the activities is in the form of data collection and group assistance. It is true that the Sinar Bahari Nain group has been facilitated in receiving assistance for capital stimulus for creative economy businesses. Assistance to community groups needs to be carried out routinely and attached after the provision of assistance and supervised in its use.